2018
DOI: 10.1007/s10664-018-9673-y
|View full text |Cite
|
Sign up to set email alerts
|

Security code smells in Android ICC

Abstract: Android Inter-Component Communication (ICC) is complex, largely unconstrained, and hard for developers to understand. As a consequence, ICC is a common source of security vulnerability in Android apps. To promote secure programming practices, we have reviewed related research, and identified avoidable ICC vulnerabilities in Android-run devices and the security code smells that indicate their presence. We explain the vulnerabilities and their corresponding smells, and we discuss how they can be eliminated or mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In this category we also found cases related to CWE-798: Use of Hard-coded Credentials, such as commit f92221f from the UserLAnd app. 13 These cases are mostly due to hard-coded credentials most likely for testing purposes. However, using these credentials and having them available in repositories and/or URLs could lead to attacks.…”
Section: Invalid User Cannot Resume Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In this category we also found cases related to CWE-798: Use of Hard-coded Credentials, such as commit f92221f from the UserLAnd app. 13 These cases are mostly due to hard-coded credentials most likely for testing purposes. However, using these credentials and having them available in repositories and/or URLs could lead to attacks.…”
Section: Invalid User Cannot Resume Anmentioning
confidence: 99%
“…A paramount example is the volume of research focused on detecting vulnerabilities in Android apps (see e.g., [4,5,6,7,8,9,10,11,12,13]). The Android OS and devices have been also investigated in the context of previous studies aimed at categorizing their security weaknesses and exploits (e.g., [14,15,16,17,18,19,20,21]).…”
Section: Introductionmentioning
confidence: 99%
“…The declared permissions do not always require the use of a specific set of APIs. Moreover, permissions are not always described well in the documentation, causing developers to either lack relevant knowledge or misuse APIs during development [27], [28]. Karim et al proposed ApMiner to recommend permissions for an app based on given sets of Android APIs [29].…”
Section: A Permissions-based Android App Analysismentioning
confidence: 99%
“…We identified 28 different security smells in five different categories, and found that XSS-like Code Injection, Dynamic Code Loading, and Custom Scheme Channel are the most prevalent smells. In a follow-up work, we studied the prevalence of Inter-Component Communication (ICC)-related security smells in more than 700 open-source apps, and manually inspected around 15% of the apps to assess the extent to which identifying such smells uncovers ICC security vulnerabilities [12]. We found that almost all apps suffer from the Common Task Affinity smell, and that Unauthorized Intent and Custom Scheme Channel are prevalent among mobile apps.…”
Section: Related Workmentioning
confidence: 99%